2003
DOI: 10.1067/mva.2003.215
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of hemodialysis-related central venous stenosis or occlusion: Another option to maintain vascular access

Abstract: Decompression of the femoral vein enables preservation of vascular graft patency and improves symptoms of venous hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…It has also been suggested that it is more cost-effective to create a new graft when several endovascular interventions at short intervals are necessary to maintain patency. 19 In patients with no remaining upper limb access options, the most commonly used alternatives are a axillary loop, long saphenous vein loop to the femoral artery, transposition to the popliteal artery, or a loop graft at the femoral triangle. A series of axillary loop accesses with a 12-month primary patency rate of 51% and a secondary patency rate of 80% at 18 months was recently reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that it is more cost-effective to create a new graft when several endovascular interventions at short intervals are necessary to maintain patency. 19 In patients with no remaining upper limb access options, the most commonly used alternatives are a axillary loop, long saphenous vein loop to the femoral artery, transposition to the popliteal artery, or a loop graft at the femoral triangle. A series of axillary loop accesses with a 12-month primary patency rate of 51% and a secondary patency rate of 80% at 18 months was recently reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several complex (exotic, extra-anatomic) access procedures in patients with difficult vascular access problems have been described. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] These options include axillary loops, axillaryaxillary arteriovenous grafts, internal jugular vein bypasses, superficial femoral vein transpositions, femorofemoral arteriovenous cross over bypasses, axillary artery to popliteal vein bypasses, and femoral artery to right atrium bypasses. 3,9 The arteriovenous axillary loop graft has been reported as a possible primary vascular access procedure when no other upper limb option is feasible.…”
mentioning
confidence: 99%
“…5. Intervention should be the first choice for venous hypertension caused by central venous stenosis . However, intervention should be avoided in cases where the risk of vessel rupture by intervention is high.…”
Section: Chapter 5‐3 Venous Hypertensionmentioning
confidence: 99%
“…An alternative vascular access must be secured for continuing renal replacement therapy. Other options include repeated percutaneous transluminal balloon angioplasty with or without stent insertion, venous reconstruction, including a polytetrafluoroethylene axillary to the saphenous graft bypass [35], an atrial graft bypass [36], a switch to a lower-limb vascular access, or peritoneal dialysis.…”
Section: Discussionmentioning
confidence: 99%